MTUN Industry smart partnership produce technical expert - UMP, PNC (2019)
Malaysia Technical University Network (MTUN) is urged to continue working with the industry to ensure research output is beneficial to address industry related issues. According to Deputy Director General, Department of Higher Education, Ministry of Education, Professor Dr. Mohd Cairul Iqbal Mohd Amin, universities smart partnership particularly with MTUN should be intensified to encourage the industry to conduct research studies using the university's expertise and equipment as practiced in developed countries.